A numerical analysis of casing groove parameters on the performance of wave energy conversion device. (2018) - Halder, Paresh; Varghese, Francis Amal; Husain, Afzal; Samad, Abdus
Casing grooves in Wells turbine can enhance its performance. The present computational work has been carried out to understand the effect of casing-groove's width-to-chord (w/C) ratio on the performance of a wave energy conversion device. In this study, four different values of w/C ratio such as 0.24, 0.48, 0.64 and 0.96 were investigated. The circumferential casing groove depth (3% of the chord length) and tip clearance (1% of the chord length) were kept constant for all the cases. The flow field was analysed through discretisation of three-dimensional steady incompressible Reynolds-averaged Navier-stokes (RANS) equations with two-equation eddy viscosity turbulence closer model. The simulation results show that the w/C ratio has a significant impact on the turbine performance and the w/C = 0.64 was found to be the optimal one among the several values investigated in the present study.